Disintegration and resilience of agrarian societies in Africa - the importance of social and genetic resources: a case study on the reception of urban war refugees in the south of Guinea-Bissau - Temudo, M. P.; Schiefer, U. (Current Sociology, 2003)
The disintegration of African agrarian societies is partly caused by the dissipative economy of development aid and becomes more visible in wartime. The resilience of agrarian societies constitutes thus an important resource for the whole country. Their capacity to maintain stability and a productive agricultural potential can ensure the survival of urban populations driven from the cities in time of war. The potential for reconstruction of these agrarian societies after catastrophes depends on internal - genetic as well as social - resources and on their capacity to mobilize and to integrate external resources. The thesis of this article is that the usual package of emergency relief, rehabilitation and rural development aid does not form the most adequate approach to traumatized societies. The authors show that in the south of Guinea-Bissau during and after the armed conflict, the established interethnic network of rural populations was able to shelter a large number of urban refugees for a considerable time.